2010
DOI: 10.1080/03602550903533974
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Physico-Mechanical Properties, Water, Thermal and Chemical Ageing of Unsaturated Polyester/Turmeric Spent Composites

Abstract: Nutraceutical industrial residues are potential fillers to fabricate green or eco-friendly polymeric composite materials as they are, less costly and easily available. Attempts have been made to use turmeric spent (TS)-a nutraceutical industry waste with a high E-factor to improve need-based properties of plastics. A series of unsaturated polyester resin composites have been fabricated with different turmeric spent content viz., 5, 10, 15 and 20% w/w. The effect of amount of filler content on tensile strength,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Our research school is the first to report the use of NIS as filler material in the fabrication of thermoplastic and thermoset composites [33,[54][55][56][57][58][59][60]65] and for the use as effective adsorbents for remediation of Congo red, methylene blue and ethidium bromide dyes [32,53,64]. Despite myriad research papers reported the use of low-cost agriculture waste as biosorbent for the remediation of toxic dyes; very limited information is available about the use of dye adsorbed biosorbent commonly known as "sludge".…”
Section: Introductionmentioning
confidence: 99%
“…Our research school is the first to report the use of NIS as filler material in the fabrication of thermoplastic and thermoset composites [33,[54][55][56][57][58][59][60]65] and for the use as effective adsorbents for remediation of Congo red, methylene blue and ethidium bromide dyes [32,53,64]. Despite myriad research papers reported the use of low-cost agriculture waste as biosorbent for the remediation of toxic dyes; very limited information is available about the use of dye adsorbed biosorbent commonly known as "sludge".…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, wood fiber-reinforced plastic composites or so-called wood-plastic composites (WPCs) have attracted significant interest and they are replacing wood in many fields, including a variety of building products, automotive, infrastructure, and other industrial applications, because of their specific advantages such as high strength, low cost, biodegradability, low water absorption and thickness swelling, and better recyclability [1][2][3][4]. In general, the properties of WPCs depend on various factors, including the inherent properties of the constituent materials, interactions among these materials, and processing methods [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Adding of lignocellulosic materials to plastics offer many environmental friendly benefits like making the final product lightweight, decreasing erosion of the manufacturing machinery, low cost, biodegradability, and absence/minimization of production of residue or toxic by‐products when burnt. Our research school has reported on this aspect .…”
Section: Introductionmentioning
confidence: 91%